VATS Lobectomy: Surgical Evolution from Conventional VATS to Uniportal Approach - Diego Gonzalez-Rivas (The Scientific World Journal)
There is no standardized technique for the VATS lobectomy, though most centres use 2 ports and add a utility incision. However, the procedure can be performed by eliminating the two small ports and using only the utility incision with similar outcomes. Since 2010, when the uniportal approach was introduced for major pulmonary resection, the technique has been spreading worldwide. The single-port technique provides a direct view to the target tissue. The conventional triple port triangulation creates a new optical plane with genesis of dihedral or torsional angle that is not favorable with standard two-dimension monitors. The parallel instrumentation achieved during single-port approach mimics inside the maneuvers performed during open surgery. Furthermore, it represents the less invasive approach possible, and avoiding the use of trocar, we minimize the compression of the intercostal nerve. Further development of new technologies like sealing devices for all vessels and fissure, robotic arms that open inside the thorax, and wireless cameras will facilitate the uniportal approach to become the standard surgical procedure for pulmonary resection in most thoracic departments.